Pureed banana inflorescences and their potential uses in dysphagia diets - Panyayong, Chunkamol; Srikaeo, Khongsak (Journal of Food Technology Research, 2023)
This study aimed to develop new vegetable purees derived from banana inflorescences as well as recipes suitable for individuals suffering from dysphagia. The effects of hydrocolloids (modified tapioca starch; MTS, gum acacia; GA, xanthan gum; XG, carboxymethyl cellulose; CMC, and gelatin; GEL) on the quality of purees were investigated. Banana inflorescences turned out to be a good choice for the preparation of purees that complied with “Level 4 Pureed Food for Adults” as examined by the International Dysphagia Diet Standardization Initiative (IDDSI) methods. The addition of XG and CMC to the purees improved their qualities. However, the effects of hydrocolloids depended on the types and concentrations used. Some hydrocolloids, such as GA and GEL, have been discovered to be unsuitable. The kale leaf, pumpkin, and Riceberry-flavored soups, made from banana inflorescence purees as a main ingredient, were successfully prepared. All recipes adhered to the IDDSI guidelines for “Level 3 Liquidized Food for Adults”. The finding in this study could promote the use of banana inflorescence as a potential ingredient for purees suitable to be used as dysphagia diets.